Pre-screening of induced seismicity risks for CO2 injection at Trüllikon, Switzerland - Ryan Schultz; Antonio Pio Rinaldi; Philippe Roth; Herfried Madritsch; Thanushika Gunatilake; Stefan Wiemer (International Journal of Greenhouse Gas Control, 2024)

Exposure manipulation strategies for balancing computational efficiency and precision in seismic risk analysis - Athanasios N. Papadopoulos; Philippe Roth; Laurentiu Danciu (Bulletin of Earthquake Engineering, 2024)
Exposure models for regional seismic risk assessment often place assets at the centroids of administrative units for which data are available. At best, a top-down approach is followed, where such data are spatially disaggregated over a denser spatial grid, using proxy datasets such as the distribution of population or the density of night-time lights. The resolution of the spatial grid is either dictated by the resolution of the proxy dataset, or by constraints in computational resources. On the other hand, if a building-by-building database is available, it often needs to be aggregated and brought to a resolution that ensures acceptable calculation runtimes and memory demands. Several studies have now investigated the impact of exposure aggregation on loss estimates. Herein, unlike previous attempts, we can leverage upon an extensive building-by-building database for the Swiss territory, which we can use as ground truth. We firstly proceed to assess the aggregation-induced errors of standard risk metrics at different spatial scales. Then a new strategy for performing said aggregation is proposed, relying on a K-means clustering of site parameters and a reduction of the loss ratio uncertainty for aggregated assets. These interventions are designed with the objective of minimizing errors, while keeping the computational cost manageable.

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Low circulating adropin concentrations predict increased risk of cognitive decline in community-dwelling older adults - Geetika Aggarwal; John E. Morley; Bruno Vellas; Andrew D. Nguyen; Andrew A. Butler; Sophie Guyonnet; Isabelle Carrié; Lauréane Brigitte; Catherine Faisant; Françoise Lala; Julien Delrieu; Hélène Villars; et al. (GeroScience, 2023)
The secreted peptide adropin is highly expressed in human brain tissues and correlates with RNA and proteomic risk indicators for dementia. Here we report that plasma adropin concentrations predict risk for cognitive decline in the Multidomain Alzheimer Preventive Trial (ClinicalTrials.gov Identifier, NCT00672685; mean age 75.8y, SD = 4.5 years, 60.2% female, n = 452). Cognitive ability was evaluated using a composite cognitive score (CCS) that assessed four domains: memory, language, executive function, and orientation. Relationships between plasma adropin concentrations and changes in CCS (∆CCS) were examined using Cox Proportional Hazards Regression, or by grouping into tertiles ranked low to high by adropin values and controlling for age, time between baseline and final visits, baseline CCS, and other risk factors (e.g., education, medication, APOE4 status). Risk of cognitive decline (defined as a ∆CCS of − 0.3 or more) decreased with increasing plasma adropin concentrations (hazard ratio = 0.873, 95% CI 0.780–0.977, P = 0.018). Between adropin tertiles, ∆CCS was significantly different ( P = 0.01; estimated marginal mean ± SE for the 1st to 3rd tertile, − 0.317 ± 0.064; − 0.275 ± 0.063; − 0.042 ± 0.071; n = 133,146, and 130, respectively; P < 0.05 for 1st vs. 2nd and 3rd adropin tertiles). Normalized plasma Aß 42/40 ratio and plasma neurofilament light chain, indicators of neurodegeneration, were significantly different between adropin tertile. These differences were consistent with reduced risk of cognitive decline with higher plasma adropin levels. Overall, these results suggest cognitive decline is reduced in community-dwelling older adults with higher circulating adropin levels. Further studies are needed to determine the underlying causes of the relationship and whether increasing adropin levels can delay cognitive decline.

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)

Prevalence and Phylogenetic Analysis of Hepatitis B in Captive and Wild-Living Pileated Gibbons (Hylobates pileatus) in Cambodia - Nicole Leroux; Janin Nouhin; Sophearot Prak; Bunthoeun Roth; François Rouet; Philippe Dussart; Nick Marx (International Journal of Primatology, 2020)

RETRACTED ARTICLE: Omega-3 fatty acid levels in red blood cell membranes and physical decline over 3 years: longitudinal data from the MAPT study - Bertrand Fougère; Sabine Goisser; Christelle Cantet; Gaëlle Soriano; Sophie Guyonnet; Philipe De Souto Barreto; Matteo Cesari; Sandrine Andrieu; Bruno Vellas; Bruno Vellas; Sophie Guyonnet; Isabelle Carrié; et al. (GeroScience, 2017)

Gut microbiota richness promotes its stability upon increased dietary fibre intake in healthy adults - Julien Tap; Jean‐Pierre Furet; Martine Bensaada; Catherine Philippe; Hubert Roth; Sylvie Rabot; Omar Lakhdari; Vincent Lombard; Bernard Henrissat; Gérard Corthier; Eric Fontaine; Joël Doré; et al. (Environmental Microbiology, 2015)
Summary Gut microbiota richness and stability are important parameters in host–microbe symbiosis. Diet modification, notably using dietary fibres, might be a way to restore a high richness and stability in the gut microbiota. In this work, during a 6‐week nutritional trial, 19 healthy adults consumed a basal diet supplemented with 10 or 40 g dietary fibre per day for 5 days, followed by 15‐day washout periods. Fecal samples were analysed by a combination of 16S r RNA gene pyrosequencing, intestinal cell genotoxicity assay, metatranscriptomics sequencing approach and short‐chain fatty analysis. This short‐term change in the dietary fibre level did not have the same impact for all individuals but remained significant within each individual gut microbiota at genus level. Higher microbiota richness was associated with higher microbiota stability upon increased dietary fibre intake. Increasing fibre modulated the expression of numerous microbiota metabolic pathways such as glycan metabolism, with genes encoding carbohydrate‐active enzymes active on fibre or host glycans. High microbial richness was also associated with high proportions of Prevotella and Coprococcus species and high levels of caproate and valerate. This study provides new insights on the role of gut microbial richness in healthy adults upon dietary changes and host microbes' interaction

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.